NF-κB signaling and the tumor microenvironment in osteosarcoma: implications for immune evasion and therapeutic resistance - Shi, Shaoyan; Ou, Xuehai; Liu, Chao; Li, Rui; Zheng, Qianjin; Hu, Leiming (Frontiers in Immunology, 2025)
Osteosarcoma, a highly aggressive malignancy with a generally poor prognosis, is characterized by tumor cells’ ability to evade immune responses and resist treatment. The nuclear transcription factor NF-κB signaling pathway is crucial in regulating inflammatory and immune reactions. It occupies a central position in the development of the osteosarcoma tumor microenvironment. This research aimed to explore how NF-κB influences the recruitment and polarization of tumor-associated macrophages and myeloid-derived suppressor cells, both of which contribute to immunosuppression. Furthermore, NF-κB facilitates immune surveillance evasion in osteosarcoma cells by altering the expression of immune checkpoint molecules, such as PD-L1. It also enhances tumor cell resistance to chemotherapy and radiotherapy by activating anti-apoptotic signaling pathways and exacerbating treatment-induced inflammation. Potential therapeutic approaches include using NF-κB inhibitors, possibly in combination with immune checkpoint inhibitors, to overcome tumor cell resistance mechanisms and reshape antitumor immune responses. A thorough examination of NF-κB’s role in osteosarcoma development is expected to yield novel clinical treatment strategies, and significantly improve patient prognosis by targeting this key signaling pathway.